Pelatihan Manajemen Risiko Bisnis Pada UMKM Teluk Pucung Bekasi - Suhardoyo Suhardoyo; Rohani Lestari; Popon Rabia Adawia; Feliona Astika (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2023)
Micro, Small and Medium Enterprises (MSMEs) are the biggest supporter of the creative economy for the Indonesian economy. MSME players must be able to develop their business to be able to carry out this. The digital era has the potential to create opportunities and risks for business people and organizations. In every business, risks will always be faced by business actors because of uncertainty which results in losses. Internal and external events that have an impact on achieving the goals of MSMEs must be identified, and risks and opportunities must be differentiated. In the business world, knowledge about risk management is an important element in business management. With good management, a business organization will be able to avoid losses and even bankruptcy. Likewise, small, micro and medium enterprises that do not have sufficient capital and whose operations are not optimal are very vulnerable to changes in risk. Events that cause losses, which are usually called peril, can occur unexpectedly and can arise from various sources. The problem is how to overcome these risks so that business operations are not disrupted. Risks are analyzed by considering likelihood and impact as a basis for determining how they can be managed. Therefore, by providing an understanding of risk management, it is hoped that MSMEs will be able to know how to implement risk management in business to avoid losses. PM activities are held offline or face to face on holidays so as not to disturb the work time of the Teluk Pucung MSMEs, while the output of PM activities is in the form of press releases in online print media and also publications in community service journals